PROBLEMATIKA PENGHAPUSAN GOLONGAN PENDUDUK TERHADAP PERALIHAN HAK ATAS TANAH DI INDONESIA - Permadi, Iwan; Yahya, Muhamad; Muttaqin, Irsyadul (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research explores the challenges in eliminating population categorization in the transfer of land rights. This change is highlighted due to protests and evaluations of the perceived discriminatory articles that identify race, groups, and ethnicity. The grouping in the creation of inheritance certificates is considered to create legal politics contrary to the spirit of independence, preserving differences seen as a legacy of Dutch colonialism. This research adopts a normative juridical method. The findings indicate that the delegation of tasks and authority, as well as the classification of the population in the process of creating inheritance certificates, essentially provides legal certainty to society. Separation based on archives and historical data updates has a positive impact on the land rights transfer process. This classification strengthens the legal framework related to land registration and certification, making it more secure and efficient. Conversely, the absence of classification in the creation of inheritance certificates can create legal uncertainty in the registration of land rights transfer due to the lack of clarity in data, information, and historical developments that need to be updated and recertified.